Nowcasting economic growth in India: The role of rainfall - Tara Iyer; Abhijit Sen Gupta (Asian Development Bank (ADB), 2019)
This study provides a toolkit to nowcast, or produce early estimates of, gross domestic product (GDP) growth in India. We use a dynamic factor model (DFM) to nowcast GDP growth in India on a quarterly basis from January 2000 to December 2018. The DFM methodology offers a powerful and tractable means of nowcasting economic growth while accounting for mixed-frequency data, which is data released on different dates, and missing time series. The specified DFM, which includes six quarterly indicators and 12 higher-frequency monthly variables, is able to effectively nowcast growth in India. The variables in the framework are drawn from the real, monetary, financial, and external sectors in India and selected to represent aggregate economic activity. There are several interesting results in the study. A key finding is that rainfall has high predictive content for GDP growth in India, a novel result from the viewpoint of the existing nowcasting literature.
Keywords: C32; C53; Q56; 330; dynamic factor model; GDP growth; India; nowcasting; rainfall